2017
DOI: 10.1162/evco_a_00186
|View full text |Cite
|
Sign up to set email alerts
|

A Hidden Markov Model Approach to the Problem of Heuristic Selection in Hyper-Heuristics with a Case Study in High School Timetabling Problems

Abstract: Operations research is a well established field that uses computational systems to support decisions in business and public life. Good solutions to operations research problems can make a large difference to the efficient running of businesses and organisations and so the field often searches for new methods to improve these solutions. The high school timetabling problem is an example of an operations research problem and is a challenging task which requires assigning events and resources to time slots subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

6
4

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 45 publications
0
24
0
2
Order By: Relevance
“…Furthermore, based on our findings the use of greedy approach for initialising the solutions of medium and large size instances leads to improved performance. The application of advanced algorithms, such as hyper-heuristics [15], [16] and evolutionary algorithms [17]- [19], is suggested for further research in order to escape local minima and achieve improved solutions for medium and large instances.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on our findings the use of greedy approach for initialising the solutions of medium and large size instances leads to improved performance. The application of advanced algorithms, such as hyper-heuristics [15], [16] and evolutionary algorithms [17]- [19], is suggested for further research in order to escape local minima and achieve improved solutions for medium and large instances.…”
Section: Discussionmentioning
confidence: 99%
“…We propose a sequence-based selection hyper-heuristic utilising a hidden Markov model [4,5]. This adaptive approach maintains scores representing the probability of choosing a low level heuristic considering the previously invoked heuristic, learning effective sequences of low level heuristics to employ.…”
Section: Optimisation Methodsmentioning
confidence: 99%
“…A new field of hyper-heuristic methods embedding data science techniques has recently been developed (Asta andÖzcan, 2015). Experiments on a hyper-heuristic benchmark framework (Kheiri and Keedwell, 2015), urban transit route design problem (Ahmed et al, 2019), wind farm layout optimization problem (Wilson et al, 2018), high school timetabling problem (Kheiri and Keedwell, 2017) and on water distribution optimization problem (Kheiri et al, 2015) have shown that applying a sequence of low level heuristics can potentially improve the quality of solutions more than those that simply select and apply a single low level heuristic.…”
Section: A Sequence-based Selection Hyper-heuristic (Team: Akhe)mentioning
confidence: 99%